The relationship between the general government debt and the gross domestic product: a case for Portugal - Almeida, João Carlos Francisco de (2018)
This dissertation analysis empirically the relationship between PIB, public debt and the current account balance in Portugal. In this study were used 37 yearly observations for the between comprehended between 1980 and 2016. During the financial crisis of 2008, the levels of public debt raised sharply being considered one of the main factors for the slow growth or even decrease of GDP. Recently, these effects were proven to be close to nil in advanced economies. However, the increase in public debt should not be stimulated, since it would lead to a higher volatility, which could be one of the reasons for slower GDP growth rates. In a VECM model, it was possible to conclude the presence of a long-term relationship between the variables. Additionally, we had no evidence of Granger causality. Therefore, neither the public debt nor the current account balance could cause slow GDP growth rates in the short-run.